A Brief Review on the Sensor Measurement Solutions for the Ten-Meter Walk Test - Pires, Ivan Miguel; Lopes, Eurico; Villasana, María Vanessa; Garcia, Nuno M; Zdravevski, Eftim; Ponciano, Vasco (Multidisciplinary Digital Publishing Institute, 2021)
The wide-spread use of wearables and the adoption of the Internet of Things (IoT) paradigm provide an opportunity to use mobile-device sensors for medical applications. Sensors available in the commonly used devices may inspire innovative solutions for physiotherapy striving for accurate and early identification of various pathologies. An essential and reliable performance measure is the ten-meter walk test, which is employed to determine functional mobility, gait, and vestibular function. Sensor-based approaches can identify the various test phases and their segmented duration, among other parameters. The measurement parameter primarily used is related to the tests’ duration, and after identifying patterns, a variety of physical treatments can be recommended. This paper reviews multiple studies focusing on automated measurements of the ten-meter walk test with different sensors. Most of the analyzed studies measure similar parameters as traditional methods, such as velocity, duration, and other involuntary and dangerous patients’ movements after stroke. That provides an opportunity to measure different parameters that can be later fed into machine learning models for analyzing more complex patterns.
Keywords: ten-meter walk test; measurement; inertial sensors; physiotherapy; review